2013
DOI: 10.1136/bcr-2013-009973
|View full text |Cite
|
Sign up to set email alerts
|

Infected total knee arthroplasty due to postoperative wound contamination withPasteurella multocida

Abstract: Pasteurella multocidais a small Gram-negative bacterium comprising part of the normal gastrointestinal and nasopharyngeal flora of domestic pets, such as dogs and cats. It rarely causes infection in humans. Previous reports ofP multocidacausing prosthetic joint infection have described either haematogenous spread of infection from a distant site through a scratch or bite, or reactivation of infection from a previous injury. We report a case of acute total knee arthroplasty joint infection becoming acutely infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous reports have described either a hematogenous infection after a scratch or bite at a remote site or reactivation of previous infection [8]. Despite surgical excision and effective antibiotic therapy, secondary endocarditis and joint infection occurred in our patient.…”
Section: Discussionmentioning
confidence: 60%
“…Previous reports have described either a hematogenous infection after a scratch or bite at a remote site or reactivation of previous infection [8]. Despite surgical excision and effective antibiotic therapy, secondary endocarditis and joint infection occurred in our patient.…”
Section: Discussionmentioning
confidence: 60%
“…Risk factors for this unique causative organism include advanced age, diabetes, rheumatoid arthritis, obesity, immunosuppression, previous surgical intervention, renal insufficiency, blood loss during surgery, and postoperative drainage [ 39 ]. Our review of the literature identified 34 documented cases of periprosthetic knee and hip infections with P. multocida [ [2] , [3] , [5] , [6] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ]. In the majority of these cases, the patients presented similarly to ours with a clinical picture including pain, an effusion (if at the knee), drainage, fever, and an elevated peripheral white blood cell count, ESR, and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Zoonotic infections make up a very small percentage of all PJIs. Since 1975, there have been only 29 cases of TKA prosthetic infections due to P. multocida reported in the English literature ( Table 1 ) [ 12 , 13 , 15 , 20 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. The majority (20/29, 69%) were attributed to scratch or bite from a cat or dog.…”
Section: Discussionmentioning
confidence: 99%